KESIAPSIAGAAN RUMAH TANGGA TERHADAP BENCANA BANJIR DI KECAMATAN BALEREJO, KABUPATEN MADIUN (JURNAL SPASIAL, 2021)
Household preparedness efforts are one of the preventive measures and responses taken by the community in facing the threat of flooding which can minimize the impact of a disaster if it is carried out appropriately and effectively. The purpose of this study was to determine the level of preparedness and the factors that affect the level of household preparedness against floods in Balerejo District, Madiun. The research method used is a survey method and statistical analysis. The data collection technique used a questionnaire which was distributed to respondents in Babadan Lor and Jerukgulung Village. The parameters used to measure preparedness are knowledge and attitudes towards disasters, family preparedness plans, disaster warning systems, and the ability to mobilize resources. The results showed that 45.28% of households in Babadan Lor Village and 36.17% of households in Jerukgulung Village were considered “Very Ready” to face floods. Factors that significantly influence household preparedness include gender, location of the house based on the distance between the house and the river, responsibility efficacy, sense of community, and outcome expectancy.